Success at first certificate - Duckworth, M. (Oxford University Press, 1991)
This workbook contains twenty units that are thematically linked to the twenty units of the student´s book. Each unit has a new authentic reading passage, and revises and extends the languaje and vocabulary introduced in the student´s book. The workbook also contains four complete progress test